Influence of Education on Public Perceptions of Climate Change and Disaster Risk Management Policy and Plan Formulation - Aryal, Pitambar; Pandey, Chandra Lal; Poudyal, Amod Kumar (NCWA Annual Journal, 2026)
Climate change and climate-induced disasters pose significant threats to the socio-economic well-being of communities, contributing to over 65% of disaster-related deaths annually in Nepal. Policies and plans serve as vital instruments for setting long-term vision, defining goals, designing interventions, and guiding implementation across multiple governance levels. Equally important is understanding how local communities perceive these policies and plans, as such perceptions influence ownership, effectiveness, and successful implementation. Sarawal Rural Municipality in Nawalparasi West District of Lumbini Province in Nepal is highly vulnerable to floods, drought, fires, cold waves, and heat waves each year. Floodwater inundation is a major hazard, and each year approximately 40 percent of paddy fields are destroyed due to inundation. However, this year it was affected by drought, thus climate variability and change are major concerns for them. This study examines the role of the educational level of community people in shaping community perceptions of climate risk management and disaster risk management plans and policies formulation in Sarawal Rural Municipality. Employing a quantitative research design, a total of 428 households were selected using systematic random sampling. Community perceptions were assessed through five statements measured on a five-point Likert scale, focusing on climate and disaster risk management (CRM/DRM) policies and plans. The findings indicate that educational background does not solely influence community perceptions of CRM/DRM policies and plans; rather, lived experiences play a crucial role in shaping these perceptions. The study highlights that well-designed policies and plans remain critical instruments for building community resilience and facilitating effective climate and disaster risk management, regardless of educational differences.